The afterlife of the Leiden anatomical collections - Huistra, Hieke, 1982- author.
1 online resource.
Keywords: "The Afterlife of the Leiden Anatomical Collections starts where most stories end: after death. It tells the story of thousands of body parts kept in bottles and boxes in nineteenth-century Leiden - a story featuring a struggling medical student, more than one disappointed anatomist, a monstrous child, and a glorious past. Hieke Huistra blends historical analysis, morbid anecdotes, and humour to show how anatomical preparations moved into the hands of students and researchers, and out of the reach of lay audiences. In the process, she reveals what a centuries-old collection can teach us about the future fate of the biobanks we build today"--